Contact capacity and its effect on intergroup relations - Pfister, M; Wölfer, R; Hewstone, M (SAGE Publications, 2019)
Although intergroup contact is an effective means to improve intergroup attitudes, it does not always have a positive impact on them. This study introduces contact capacity as a factor that may impede intergroup contact. Longitudinal social network data (N = 6,600; Mage = 14.87 years) was collected in Germany, the Netherlands, and Sweden and used to accurately calculate participants’ out-group, in-group, and total contact. Multilevel models (L1: students, L2: school classes) showed that the total amount of contact at Wave 1 negatively predicts individuals’ out-group friends at Wave 2 while controlling for out-group attitudes, existing out-group friendships and sociodemographic variables. An additional robustness check showed that this effect holds true for future in-group friendships. The study highlights the importance of contact capacity for whether people engage in intergroup contact and the contribution of social network analysis to contact research.